COCCIDS DAMAGE TO SCENIC TREES IN ANDIJAN ARBOROPARK AND RECREATION GARDENS (Scientific journal of the Fergana State University, 2023)
In this article, coccids belonging to the subfamily of scaly-trunky insects cause the disruption of the process of metabolism in plant tissues, they constantly feed on plant tissue sap, which slows down the growth of plants. Some leaves, twigs and branches dry up and completely dry up due to severe damage. Due to this, the attention to the study of coccids has increased, several studies have been conducted to study the species composition, distribution and biological characteristics of coccids from different regions, and the article discusses the coccids that damage ornamental trees in the Andijan arboretum and recreational parks.